2019
DOI: 10.1093/intqhc/mzz062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TeamSTEPPS on patient safety culture in a Swiss maternity ward

Abstract: Objective To assess the impact of implementation of the TeamSTEPPS teamwork improvement concept on patient safety culture. Design Pre-post culture assessment using the Hospital Survey on Patient Safety Culture, at baseline and one year after implementation of TeamSTEPPS. Setting Two maternity wards within the same 480-bed multisite teaching hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 18 publications
4
17
1
3
Order By: Relevance
“…In congruence with the current study was Staines et al 22 who concluded that after implementing the Team STEPPS, the teamwork concept significantly improved in the intervention group. In the same line were Gaston et al 23 who concluded that staff perception of teamwork and communication improved significantly after implementation of the Team STEPPS program.…”
Section: Discussionsupporting
confidence: 88%
“…In congruence with the current study was Staines et al 22 who concluded that after implementing the Team STEPPS, the teamwork concept significantly improved in the intervention group. In the same line were Gaston et al 23 who concluded that staff perception of teamwork and communication improved significantly after implementation of the Team STEPPS program.…”
Section: Discussionsupporting
confidence: 88%
“…Besides, this was because the control group did not receive any training, which means there was no stimulus in the group. 17 This was in accordance with the Law of Response by Analogy proposed by Thorndike, which explained that individuals tend to react and respond to the events they face. Thus, without any stimulus in the form of training to improve nurse communication in the control group, a person would only display existing cognitive skills.…”
Section: Resultssupporting
confidence: 86%
“…This was in line with Shaw’s research which stated that there was no significant difference between pre- and post-survey, especially in communication perception variables, due to limited training time. 17 The duration of the workshop was less than the AHRQ standard, as this study only ran for 2 hours. Meanwhile, based on AHRQ standards, the TeamSTEPPS workshop can be held for 4-6 hours on the second day, after giving the material on the first day.…”
Section: Resultsmentioning
confidence: 99%
“…These differences must be addressed, with interventions tailored to the respective institutions. There is ample evidence that interventions aimed at enhancing the teamwork climate among health care providers improve patients' outcomes; 29,30 increase providers' satisfaction, 31 possibly reducing their burnout; and improve clinical performance 32,33 and patients' safety 34 across different clinical environments. This evidence holds true particularly in oncology clinical settings, where patients' care depends critically on good collaboration and coordination among medical teams.…”
Section: Discussionmentioning
confidence: 99%